Conversions related to adhesions in abdominal surgery. Robotic versus laparoscopic approach: A multicentre experience. Issue 2 (16th November 2020) - Milone, Marco; de'Angelis, Nicola; Beghdadi, Nassiba; Brunetti, Francesco; Manigrasso, Michele; De Simone, Giuseppe; Servillo, Giuseppe; Vertaldi, Sara; De Palma, Giovanni Domenico
Abstract: Background: An advantage of robotic surgery over laparoscopy is the lower rate of unplanned conversion. One of the implicated reasons for conversion is adhesions from previous abdominal surgeries (PASs). Methods: A comparative analysis of 98 patients with history of open PAS treated by laparoscopic or robotic surgery was performed. Primary endpoint was the rate of conversion to open surgery related to adhesiolysis. Secondary endpoints were short‐term outcomes and complications. Results: Conversion rate specifically related to adhesiolysis was significantly lower in robotic group (13 for laparoscopic group vs. 2 for robotic group; p = 0.046). Conversions occurred during adhesiolysis were significantly related to severity of adhesions expressed by peritoneal adhesion index (PAI) score ( p < 0.001), number of abdominal areas involved by adhesions ( p < 0.001) and severity of PAI into the target area of surgical intervention ( p = 0.021). Conclusions: Benefits of robotic surgery are more noticeable in performing procedures with increasing technical difficulties.